Negative photosensitive polyamic acid, photosensitive resin and preparation method and application of negative photosensitive polyamic acid and photosensitive resin
By introducing norbornene dicarboxylic anhydride at the chain end of the polyamic acid molecule and combining polymercaptans and photoinitiators to form a negative photosensitive polyamide system, it solves the difficulty of existing materials to maintain thermal science when improving the resolution and sensitivity of photo patterning. The performance problem is to achieve high resolution and high thermal stability lithographic patterns.
Patent Information
- Application Number
- CN202411809282.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-02-14
AI Technical Summary
While existing negative photosensitive polyimide materials improve the resolution and sensitivity of light patterning, it is difficult to maintain the thermal and mechanical properties of the polymer, and the challenges of balancing the properties of these materials are great.
By introducing norbornene dicarboxylic anhydride at the chain end of the polyamic acid molecular chain, an alkenyl crosslinking point is formed, and a negative photosensitive polyamide system is formed, achieving a high-resolution photolithography pattern. , while improving the thermal stability of the material.
It is achieved to improve the resolution and sensitivity of the lithographic pattern while maintaining the thermal properties of the polymer, and the preparation method is simple and the patterned optical film material with uniform thickness can be controlled.
Smart Images

Figure CN119431785A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of negative photosensitive polyimide, and in particular to a negative photosensitive polyamic acid, a photosensitive resin, and a preparation method and application thereof. Background Art
[0002] Negative photosensitive polyimide is a class of materials with strong commercial sensitivity. It uses traditional polyimide as a matrix, and gives polyimide photosensitivity by introducing photosensitive groups into the molecular chain or directly adding components with photosensitive properties into the polyimide resin matrix. Negative photosensitive polyimide retains the excellent thermal properties, dielectric properties, electrical properties, mechanical properties and chemical stability of the polyimide material itself, and exhibits close adhesion with various substrate materials and good matching with semiconductor processes. It has been widely used in photoresists, integrated circuits, optoelectronic devices, electrical insulation devices and other scenarios to protect semiconductor circuits from the influence of physical and chemical conditions.
[0003] From a structural perspective, negative photosensitive polyimide can be divided into two types: intrinsic type and composite type. Composite negative photosensitive polyimide refers to a mixture of film-forming resin, photosensitive molecules (such as photoacid generator, photobase generator, dissolution inhibitor, etc.), photoinitiator, etc., which undergoes crosslinking or degradation under radiation stimulation [Hasegawa M. et al, Journal of Photopolymer Science and Technology, 2009, 22 (3): 411-415]. This type of material can usually show considerable graphic resolution, but is not very sensitive to the wavelength of the exposure light source. Intrinsic negative photosensitive polyimide is a polyimide in which photosensitive groups are directly introduced into the polyimide matrix by chemical bonding, so that photochemical reactions can be achieved without the addition of external photosensitive molecules, such as the ester-type negative photosensitive polyimide developed by Siemens of Germany [Hou HQ et al, European Polymer Journal, 1999, 35 (11): 1993-2000], and "PHOTONEECE" developed by Toray Industries, Ltd. [Bas C. et al, Journal of Polymer Science Part B: Polymer Physics, 2005, 43 (17): 2413-2426]. In the preparation process of intrinsic negative photosensitive polyimide, the structure of the intermediate product polyamic acid has a significant effect on the photopatterning behavior. Low molecular weight polyamic acid is conducive to accelerating the rate of photoinduced crosslinking between molecular chains, so that the corresponding negative photosensitive polyimide system obtains higher sensitivity, but it will sacrifice the thermal and mechanical properties of the polymer to a certain extent. Therefore, it is very important to balance the material properties of negative photosensitive polyimide and key parameters such as photopatterning resolution and sensitivity.
[0004] The thiol-ene / yne click reaction is a type of organic reaction with advantages such as high selectivity, high reaction rate, and mild reaction conditions. It can also be combined with photochemical reactions to be used in the fields of material surface patterning, polymer modification, hydrogel synthesis, coating curing, nanoimprint lithography, and electron beam lithography. Carbon-carbon double bond groups are widely available and are often used for photoinduced cross-linking modification of polymers. At present, a variety of molecules containing carbon-carbon double bond characteristic structures are used to construct negative photosensitive polyimides, such as chalcone structures and cinnamoyl structures. The characteristics of [2+2] cycloaddition reactions under light induction are used to construct cross-linking bridges between polyamic acid or polyimide, so that the polyimide exhibits good photocuring properties. By combining with a high reaction efficiency click reaction and selecting an appropriate double-bond polyimide matrix, the performance and structural range of negative photosensitive polyimide materials are expected to be significantly improved. Summary of the invention
[0005] The object of the present invention is to provide a negative photosensitive polyamic acid for preparing negative photosensitive polyimide and a preparation method thereof.
[0006] Another object of the present invention is to provide a photosensitive resin comprising negative photosensitive polyamic acid, and a preparation method and application thereof.
[0007] Another object of the present invention is to provide a photosensitive polyimide film prepared by using a photosensitive resin and cross-linked by polythiol.
[0008] Another object of the present invention is to provide a polyimide photoresist film formed by using the above-mentioned photosensitive resin and a preparation method thereof.
[0009] To this end, the technical solution of the present invention is as follows:
[0010] A negative photosensitive polyamic acid, the general chemical structure of which is as follows:
[0011]
[0012] In the formula, X is derived from a diamine monomer having at least one benzene ring or a cycloalkane structure; Y is derived from a tetracarboxylic dianhydride compound having at least one benzene ring or a cycloalkane structure; and the value of n ranges from 50 to 300.
[0013] Preferably, X in the diamine monomer adopts at least one of the following chemical structures:
[0014]
[0015] Preferably, Y in the tetracarboxylic dianhydride compound adopts at least one of the following chemical structures:
[0016]
[0017] A method for preparing the above-mentioned negative photosensitive polyamic acid, comprising the following steps: placing a mixed reaction liquid of a diamine monomer and a tetracarboxylic dianhydride compound in a nitrogen atmosphere and an ice-water bath environment to react for 6 hours to 12 hours; continuing to add norbornene dicarboxylic anhydride and reacting for 3 hours to 6 hours to cap the end; wherein the molar ratio of the diamine monomer to the tetracarboxylic dianhydride compound is 1:(0.85-0.99), and the sum of the molar amount of the anhydride of the tetracarboxylic dianhydride compound and the molar amount of the norbornene dicarboxylic anhydride is equal to the molar amount of the amino group of the diamine monomer.
[0018] Preferably, the solvent for preparing the mixed reaction liquid of the diamine monomer and the tetracarboxylic dianhydride compound is an organic solvent selected from one or more of N,N-dimethylacetamide, N,N-dimethylformamide or N-methylpyrrolidone; the amount of the organic solvent used is such that the solid content of the mixed reaction liquid is 20wt% to 40wt%.
[0019] The negative photosensitive polyamic acid has no special restrictions on the specific selection of diamine monomers and tetracarboxylic dianhydride compounds. Its main innovation lies in: using an appropriate amount of norbornene dicarboxylic anhydride to end-cap the copolymer, so that alkenyl groups are generated at the ends of the molecular chains of the copolymer, that is, cross-linking points are formed for subsequent click reactions with the thiol groups of polythiol and polythiol, while the thermal stability of the material is improved; and there is a clear limit on the amount of norbornene dicarboxylic anhydride added relative to the diamine and tetracarboxylic dianhydride compounds, so as to achieve a high-resolution photolithography pattern when preparing a polyimide film.
[0020] A photosensitive resin, comprising:
[0021] Negative photosensitive polyamic acid, which is the negative photosensitive polyamic acid as claimed in claim 1 or 2, or the negative photosensitive polyamic acid obtained by the preparation method as claimed in claim 3 or 4;
[0022] A polythiol, which is at least one of trimethylolpropane tris(3-mercaptopropionate) or pentaerythritol tetrakis(3-mercaptopropionate); the molar ratio of norbornene dicarboxylic anhydride to the polythiol used to prepare the negative photosensitive polyamic acid is (1-4):1;
[0023] The photoinitiator is at least one of benzoin dimethyl ether, Michler's ketone, 2,2-dimethoxy-2-phenylacetophenone, acyl phosphine, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone, azobisisobutyronitrile, benzophenone, bisazide compounds, and 1-[4-(thio)phenyl]-2-(O-benzoyloxime)-1,2-octanedione; the amount of the photoinitiator added is 50% of the molar amount of norbornene dicarboxylic anhydride.
[0024] A method for preparing the above-mentioned photosensitive resin comprises the following steps:
[0025] (1) preparing a negative photosensitive polyamic acid into a mixed solution having a solid content of 24 wt % to 30 wt %;
[0026] (2) Add polythiol and photoinitiator, and stir at room temperature in the dark for 1 h to 2 h.
[0027] Preferably, the solid content regulator is N,N-dimethylacetamide.
[0028] The photosensitive resin is designed based on the idea of thiol-ene click chemistry, with negative photosensitive polyamic acid as the main agent and polythiol as the cross-linking agent to form a negative photosensitive polyimide cross-linked by polythiol, and a certain amount of photoinitiator is doped to form a developable negative photosensitive polyimide system.
[0029] The photosensitive resin can be specifically applied to, but not limited to, preparing photoresist, photosensitive encapsulation adhesive, and photocurable adhesive.
[0030] A photosensitive polyimide film is formed from the photosensitive resin.
[0031] The photosensitive polyimide film is prepared by spin coating a photosensitive resin on a substrate, curing the film by ultraviolet cross-linking, and imidization of the film in sequence; wherein the substrate is preferably a quartz substrate.
[0032] The chemical structure of the photosensitive polyimide film is shown below:
[0033]
[0034] When the photosensitive resin is used as a photoresist, the preparation steps for forming a patterned polyimide film are as follows:
[0035] (1) coating a photosensitive resin on a substrate by spin coating;
[0036] (2) using a mask to partially shield the spin-coated substrate and perform UV light cross-linking and curing;
[0037] (3) washing and developing the cross-linked cured film using a developer;
[0038] (4) The developed cross-linked cured film is subjected to imidization reaction to prepare a patterned polyimide film.
[0039] Preferably, the specific steps of the spin coating film forming method are: drop the polyamic acid solution to the center of the substrate and let it stand for 5s to 20s. After the polyamic acid solution stops flowing, a coating machine with the substrate is placed on it and spin-coated at a low speed of 300r / min to 1000r / min for 5s to 15s to allow the polyamic acid solution to flow evenly and cover the entire surface. Then, spin-coat at a high speed of 1100r / min to 5000r / min for 30s to 45s to utilize the centrifugal force to balance the surface tension of the liquid, thereby finally obtaining a negative photosensitive polyamic acid film with a smooth surface and no defects.
[0040] Preferably, after the photosensitive resin is coated on the substrate, the quartz substrate coated with the polyamic acid solution is heated at 60° C. to 100° C. for 3 min to 30 min to perform a pre-drying treatment to remove most of the solvent.
[0041] Preferably, in the UV cross-linking and curing step, the UV light has a central emission wavelength of 190 nm to 400 nm and an intensity of 50 mW / cm 2 ~300mW / cm 2 ; Accordingly, the UV light exposure time is 60s to 300s.
[0042] Preferably, the developer is at least one of water, N-methylpyrrolidone, N,N-dimethylacetamide, dimethyl sulfoxide, chloroform, tetrahydrofuran, acetone, isopropanol, cyclohexanone, γ-butyrolactone, ethyl acetate, ether, n-hexane, and cyclohexane, or a mixed solution of a specified concentration with ethanol; the developing time is 10s to 60s.
[0043] Preferably, after the cross-linked cured film is washed and developed with a developer, the coated quartz substrate that has undergone development treatment is heated at 60° C. to 100° C. for 3 min to 30 min for post-drying treatment to remove the developer.
[0044] Preferably, the imidization reaction is carried out as follows: heating from 20°C to 300°C at a rate of 20°C / min under a nitrogen atmosphere, maintaining the temperatures at 100°C, 200°C and 300°C for 1 hour each, and then naturally cooling to room temperature to obtain a polyimide film.
[0045] Compared with the prior art, the present invention designs a photosensitive polyamic acid terminated with naphthalene anhydride to add an olefin group at the chain end of the polyamic acid molecular chain that can undergo a click reaction with the thiol group of a polythiol; further, based on the photosensitive polyamic acid, a polythiol and a photoinitiator are compounded to form a developable negative photosensitive polyimide system, thereby achieving the advantages of forming a polyimide film with a photolithography pattern having good thermal properties and high resolution; in addition, the material preparation method at each stage of the present invention is simple, and a patterned optical thin film material with uniform and controllable thickness can be controllably formed. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 is the thermal weight loss curve of the negative photosensitive polyimide film in Examples 1 to 4 of the present invention;
[0047] Figure 2 is a differential scanning calorimetry analysis curve of the negative photosensitive polyimide film in Examples 1 to 4 of the present invention;
[0048] Figure 3 Polarized light micrographs of the negative photosensitive polyimide films after patterning in Examples 8 to 11 of the present invention;
[0049] Figure 4 These are polarized microscopic photographs of the negative photosensitive polyimide films after patterning in Comparative Examples 1 to Example 3 of the present invention. DETAILED DESCRIPTION
[0050] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but the following embodiments are by no means intended to limit the present invention in any way.
[0051] Example 1
[0052] In a flask reaction vessel equipped with mechanical stirring and nitrogen atmosphere, 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.2809 g, 4.00 mmol) was dissolved in 11 mL N, N-dimethylacetamide, and continue to stir, after 2,2'-bis(trifluoromethyl)diaminobiphenyl is completely dissolved, hexafluorodianhydride (1.7951 g, 3.96 mmol) is added to the reaction solution in batches, and stirring is continued for 6 hours under ice-water bath conditions until the system presents a stable, transparent viscous solution; after the reaction is completed, nadic anhydride (0.0134 g, 0.08 mmol) is added to the reaction system, and stirring is continued for 4 hours; N, N-dimethylacetamide is added to the reaction solution to adjust the solid content of the solution to 24wt.%, and then trimethylolpropane tris(3-mercaptopropionate) (0.0118 g, 0.03 mmol) and photoinitiator benzoin dimethyl ether (10.3 mg, 0.04 mmol) are added to the reaction solution, and mechanical stirring is continued for 2 hours at room temperature and in the dark until all substances are evenly dispersed to obtain a photosensitive polyamic acid solution with photosensitivity;
[0053] The photosensitive polyamic acid solution was first filtered through a 0.45 μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by a spin coating method. The spin coating conditions were set as follows: low speed 600 r / min spin coating for 5 s, high speed 4000 r / min spin coating for 30 s, and then the film was placed in front of a 70°C heating table and baked for 5 min to remove most of the solvent, thereby obtaining a 1 μm thick polymer film with a non-sticky surface; then, the polymer film was placed in a central emission wavelength of 334 nm and an ultraviolet light intensity of 50 mW / cm 2 The film was exposed to an ultraviolet mercury lamp for 180 seconds to obtain a cross-linked and cured polyamic acid film; the polyamic acid film was imidized according to the following procedure: the temperature was increased from 20°C to 300°C at a rate of 20°C / min in a nitrogen atmosphere, and the temperatures were maintained at 100°C, 200°C, and 300°C for 1 hour respectively, and the polyimide film was finally obtained after natural cooling to room temperature.
[0054] Example 2
[0055] In a flask reaction vessel equipped with mechanical stirring and nitrogen atmosphere, 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.2809 g, 4.00 mmol) was dissolved in 10 mL N, N-dimethylacetamide, and continue to stir, after 2,2'-bis(trifluoromethyl)diaminobiphenyl is completely dissolved, hexafluorodianhydride (1.7225 g, 3.80 mmol) is added to the reaction solution in batches, and stirring is continued for 6 hours under ice-water bath conditions until the system presents a stable, transparent viscous solution; after the reaction is completed, nadic anhydride (0.0670 g, 0.40 mmol) is added to the reaction system, and stirring is continued for 4 hours; N, N-dimethylacetamide is added to the reaction solution to adjust the solid content of the solution to 26 wt.%, and then trimethylolpropane tris(3-mercaptopropionate) (0.0595 g, 0.13 mmol) and photoinitiator benzoin dimethyl ether (51.3 mg, 0.20 mmol) are added to the reaction solution, and mechanical stirring is continued for 2 hours at room temperature and in the dark until all substances are evenly dispersed to obtain a photosensitive polyamic acid solution with photosensitivity;
[0056] The photosensitive polyamic acid solution was first filtered through a 0.45 μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by a spin coating method. The spin coating conditions were set as follows: low speed 500 r / min for 5 s, high speed 4000 r / min for 30 s, and then the film was placed in front of a 70°C heating table and baked for 5 min to remove most of the solvent, thereby obtaining a 1 μm thick polymer film with a non-sticky surface; then, the polymer film was placed in a central emission wavelength of 334 nm and an ultraviolet light intensity of 50 mW / cm 2The film was exposed to an ultraviolet mercury lamp for 180 seconds to obtain a cross-linked and cured polyamic acid film; the polyamic acid film was imidized according to the following procedure: the temperature was increased from 20°C to 300°C at a rate of 20°C / min in a nitrogen atmosphere, and the temperatures were maintained at 100°C, 200°C, and 300°C for 1 hour respectively, and the polyimide film was finally obtained after natural cooling to room temperature.
[0057] Example 3
[0058] In a flask reaction vessel equipped with mechanical stirring and nitrogen atmosphere, 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.2809 g, 4.00 mmol) was dissolved in 9 mL N, N-dimethylacetamide, and continue to stir, after 2,2'-bis(trifluoromethyl)diaminobiphenyl is completely dissolved, hexafluorodianhydride (1.6319 g, 3.60 mmol) is added to the reaction solution in batches, and stirring is continued for 6 hours under ice-water bath conditions until the system presents a stable, transparent viscous solution; after the reaction is completed, nadic anhydride (0.1340 g, 0.80 mmol) is added to the reaction system, and stirring is continued for 4 hours; N, N-dimethylacetamide is added to the reaction solution to adjust the solid content of the solution to 28wt.%, and then trimethylolpropane tris(3-mercaptopropionate) (0.1181 g, 0.27 mmol) and photoinitiator benzoin dimethyl ether (102.5 mg, 0.40 mmol) are added to the reaction solution, and mechanical stirring is continued for 2 hours at room temperature and in the dark until all substances are evenly dispersed to obtain a photosensitive polyamic acid solution with photosensitivity;
[0059] The photosensitive polyamic acid solution was first filtered through a 0.45 μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by a spin coating method. The spin coating conditions were set as follows: low speed 500 r / min for 5 s, high speed 4000 r / min for 30 s, and then the film was placed in front of a 70°C heating table and baked for 5 min to remove most of the solvent, thereby obtaining a 1 μm thick polymer film with a non-sticky surface; then, the polymer film was placed in a central emission wavelength of 334 nm and an ultraviolet light intensity of 50 mW / cm 2 The film was exposed to an ultraviolet mercury lamp for 180 seconds to obtain a cross-linked and cured polyamic acid film; the polyamic acid film was imidized according to the following procedure: the temperature was increased from 20°C to 300°C at a rate of 20°C / min in a nitrogen atmosphere, and the temperatures were maintained at 100°C, 200°C, and 300°C for 1 hour respectively, and the polyimide film was finally obtained after natural cooling to room temperature.
[0060] Example 4
[0061] In a flask reaction vessel equipped with mechanical stirring and nitrogen atmosphere, 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.2809 g, 4.00 mmol) was dissolved in 8 mL N, N-dimethylacetamide, and continue to stir, after 2,2'-bis(trifluoromethyl)diaminobiphenyl is completely dissolved, hexafluorodianhydride (1.5412 g, 3.40 mmol) is added to the reaction solution in batches, and stirring is continued for 6 h under ice-water bath conditions until the system presents a stable, transparent viscous solution; after the reaction is completed, nadic anhydride (0.2010 g, 1.20 mmol) is added to the reaction system, and stirring is continued for 4 h; N, N-dimethylacetamide is added to the reaction solution to adjust the solid content of the solution to 30 wt.%, and then trimethylolpropane tris(3-mercaptopropionate) (0.1771 g, 0.40 mmol) and photoinitiator benzoin dimethyl ether (153.8 mg, 0.60 mmol) are added to the reaction solution, and mechanical stirring is continued for 1 h under normal temperature and light-proof conditions until all substances are evenly dispersed to obtain a photosensitive polyamic acid solution with photosensitivity;
[0062] The photosensitive polyamic acid solution was first filtered through a 0.45 μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by a spin coating method. The spin coating conditions were set as follows: low speed 500 r / min for 5 s, high speed 4000 r / min for 30 s, and then the film was placed in front of a 70°C heating table and baked for 5 min to remove most of the solvent, thereby obtaining a 1 μm thick polymer film with a non-sticky surface; then, the polymer film was placed in a central emission wavelength of 334 nm and an ultraviolet light intensity of 50 mW / cm 2 The film was exposed to an ultraviolet mercury lamp for 180 seconds to obtain a cross-linked and cured polyamic acid film; the polyamic acid film was imidized according to the following procedure: the temperature was increased from 20°C to 300°C at a rate of 20°C / min in a nitrogen atmosphere, and the temperatures were maintained at 100°C, 200°C, and 300°C for 1 hour respectively, and the polyimide film was finally obtained after natural cooling to room temperature.
[0063] Example 5
[0064] In a flask reaction vessel equipped with mechanical stirring and nitrogen atmosphere, 4,4'-diaminodiphenyl ether (0.9451 g, 4.00 mmol) was dissolved in 4 mL N, N-dimethylacetamide, and continue to stir, after 4,4'-diaminodiphenyl ether is completely dissolved, add pyromellitic anhydride (0.8289 g, 3.80 mmol) to the reaction solution in batches, and continue to stir for 6 hours under ice-water bath conditions until the system presents a stable, transparent viscous solution; after the reaction is completed, add nadic anhydride (0.0670 g, 0.40 mmol) to the reaction system, and continue to stir the reaction for 4 hours; add N, N-dimethylacetamide to the reaction solution to adjust the solid content of the solution to 26wt.%, then add pentaerythritol tetrakis (3-mercaptopropionate) (0.0489 g, 0.10 mmol) and photoinitiator Michler's ketone (53.7 mg, 0.20 mmol) to the reaction solution, and continue to mechanically stir for 1 hour at room temperature and in the dark until all substances are evenly dispersed to obtain a photosensitive polyamic acid solution with photosensitivity;
[0065] The photosensitive polyamic acid solution was first filtered through a 0.45 μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by a spin coating method. The spin coating conditions were set as follows: low speed 500 r / min for 5 s, high speed 4000 r / min for 30 s, and then the film was placed in front of a 70°C heating table and baked for 5 min to remove most of the solvent, thereby obtaining a 1 μm thick polymer film with a non-sticky surface; then, the polymer film was placed in a central emission wavelength of 334 nm and an ultraviolet light intensity of 50 mW / cm 2 The film was exposed to an ultraviolet mercury lamp for 180 seconds to obtain a cross-linked and cured polyamic acid film; the polyamic acid film was imidized according to the following procedure: the temperature was increased from 20°C to 300°C at a rate of 20°C / min in a nitrogen atmosphere, and the temperatures were maintained at 100°C, 200°C, and 300°C for 1 hour respectively, and the polyimide film was finally obtained after natural cooling to room temperature.
[0066] Example 6
[0067] In a flask reaction vessel equipped with mechanical stirring and nitrogen atmosphere, p-phenylenediamine (0.4326 g, 4.00 mmol) was dissolved in 4 mL N, N-dimethylformamide, and continue to stir. After the p-phenylenediamine is completely dissolved, 3, 3'4, 4'-biphenyltetracarboxylic dianhydride (1.1180 g, 3.80 mmol) is added to the reaction solution in batches, and the mixture is stirred for 6 hours in an ice-water bath until the system presents a stable, transparent viscous solution. After the reaction is completed, nadic anhydride (0.0670 g, 0.40 mmol) is added to the reaction system, and the reaction is stirred for 4 hours. N, N-dimethylacetamide is added to the reaction solution to adjust the solid content of the solution to 26 wt.%, and then pentaerythritol tetrakis (3-mercaptopropionate) (0.0489 g, 0.10 mmol) and photoinitiator Michler's ketone (53.7 mg, 0.20 mmol) are added to the reaction solution, and mechanical stirring is continued for 1 hour at room temperature and in the dark until all substances are evenly dispersed to obtain a photosensitive polyamic acid solution with photosensitivity.
[0068] The photosensitive polyamic acid solution was first filtered through a 0.45 μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by a spin coating method. The spin coating conditions were set as follows: low speed 500 r / min for 5 s, high speed 4000 r / min for 30 s, and then the film was placed in front of a 70°C heating table and baked for 5 min to remove most of the solvent, thereby obtaining a 1 μm thick polymer film with a non-sticky surface; then, the polymer film was placed in a central emission wavelength of 334 nm and an ultraviolet light intensity of 50 mW / cm 2 The film was exposed to an ultraviolet mercury lamp for 180 seconds to obtain a cross-linked and cured polyamic acid film; the polyamic acid film was imidized according to the following procedure: the temperature was increased from 20°C to 300°C at a rate of 20°C / min in a nitrogen atmosphere, and the temperatures were maintained at 100°C, 200°C, and 300°C for 1 hour respectively, and the polyimide film was finally obtained after natural cooling to room temperature.
[0069] Example 7
[0070] In a flask reaction vessel equipped with mechanical stirring and nitrogen atmosphere, 4,4'-methylenebis(2-methylcyclohexylamine) (0.9053 g, 4.00 mmol) was dissolved in 4 mL N, N-dimethylformamide, and continued to stir, after 4,4'-methylenebis(2-methylcyclohexylamine) was completely dissolved, 1,2,4,5-cyclohexanetetracarboxylic dianhydride (0.8518 g, 3.80 mmol) was added to the reaction solution in batches, and continued to stir for 6 hours under ice-water bath conditions until the system presented a stable, transparent viscous solution; after the reaction was completed, nadic anhydride (0.0670 g, 0.40 mmol) was added to the reaction system, and continued to stir the reaction for 4 hours; N, N-dimethylacetamide was added to the reaction solution to adjust the solid content of the solution to 26 wt.%, and then pentaerythritol tetrakis(3-mercaptopropionate) (0.0489 g, 0.10 mmol) and photoinitiator Michler's ketone (53.7 mg, 0.20 mmol) were added to the reaction solution, and mechanical stirring was continued for 1 hour under light-proof conditions until all substances were evenly dispersed to obtain a photosensitive polyamide acid solution with photosensitivity;
[0071] The photosensitive polyamic acid solution was first filtered through a 0.45 μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by a spin coating method. The spin coating conditions were set as follows: low speed 500 r / min for 5 s, high speed 4000 r / min for 30 s, and then the film was placed in front of a 70°C heating table and baked for 5 min to remove most of the solvent, thereby obtaining a 1 μm thick polymer film with a non-sticky surface; then, the polymer film was placed in a central emission wavelength of 334 nm and an ultraviolet light intensity of 50 mW / cm 2 The film was exposed to an ultraviolet mercury lamp for 180 seconds to obtain a cross-linked and cured polyamic acid film; the polyamic acid film was imidized according to the following procedure: the temperature was increased from 20°C to 300°C at a rate of 20°C / min in a nitrogen atmosphere, and the temperatures were maintained at 100°C, 200°C, and 300°C for 1 hour respectively, and the polyimide film was finally obtained after natural cooling to room temperature.
[0072] Example 8
[0073] In a flask reaction vessel equipped with mechanical stirring and nitrogen atmosphere, 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.2809 g, 4.00 mmol) was dissolved in 11 mL N, N-dimethylacetamide, and continue to stir, after 2,2'-bis(trifluoromethyl)diaminobiphenyl is completely dissolved, hexafluorodianhydride (1.7951 g, 3.96 mmol) is added to the reaction solution in batches, and stirring is continued for 6 hours under ice-water bath conditions until the system presents a stable, transparent viscous solution; after the reaction is completed, nadic anhydride (0.0134 g, 0.08 mmol) is added to the reaction system, and stirring is continued for 4 hours; N, N-dimethylacetamide is added to the reaction solution to adjust the solid content of the solution to 24wt.%, and then trimethylolpropane tris(3-mercaptopropionate) (0.0118 g, 0.03 mmol) and photoinitiator benzoin dimethyl ether (10.3 mg, 0.04 mmol) are added to the reaction solution, and mechanical stirring is continued for 2 hours under light-proof conditions until all substances are evenly dispersed to obtain a photosensitive polyamic acid solution with photosensitivity;
[0074] The photosensitive polyamic acid solution was first filtered through a 0.45 μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by a spin coating method. The spin coating conditions were set as follows: low speed 500 r / min for 5 s, high speed 4000 r / min for 30 s, and then the film was placed in front of a 70°C heating table and baked for 5 min to remove most of the solvent, thereby obtaining a 1 μm thick polymer film with a non-sticky surface; then, the top of the polymer film was shielded with a mask and placed under a central emission wavelength of 334 nm and an ultraviolet light intensity of 50 mW / cm 2 The film was exposed to an ultraviolet mercury lamp for 180 seconds, then developed at room temperature with a mixed solution of ethanol and water in a volume ratio of 6:5 as a developer for 25 seconds, then washed with deionized water, and finally dried at 80°C for 5 minutes to obtain a polyamic acid film with a clear cured pattern and good adhesion to the substrate; the polyamic acid film was imidized according to the following procedure: heated from 20°C to 300°C at a rate of 20°C / min in a nitrogen atmosphere, and maintained at 100°C, 200°C, and 300°C for 1 hour respectively, and finally cooled naturally to room temperature to obtain a polyimide film with a patterned surface.
[0075] Example 9
[0076] In a flask reaction vessel equipped with mechanical stirring and nitrogen atmosphere, 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.2809 g, 4.00 mmol) was dissolved in 10 mL N, N-dimethylacetamide, and continue to stir, after 2,2'-bis(trifluoromethyl)diaminobiphenyl is completely dissolved, hexafluorodianhydride (1.7225 g, 3.80 mmol) is added to the reaction solution in batches, and stirring is continued for 6 hours under ice-water bath conditions until the system presents a stable, transparent viscous solution; after the reaction is completed, nadic anhydride (0.0670 g, 0.40 mmol) is added to the reaction system, and stirring is continued for 4 hours; N, N-dimethylacetamide is added to the reaction solution to adjust the solid content of the solution to 26 wt.%, and then trimethylolpropane tris(3-mercaptopropionate) (0.0595 g, 0.13 mmol) and photoinitiator benzoin dimethyl ether (51.3 mg, 0.20 mmol) are added to the reaction solution, and mechanical stirring is continued for 2 hours under light-proof conditions until all substances are evenly dispersed to obtain a photosensitive polyamic acid solution with photosensitivity;
[0077] The photosensitive polyamic acid solution was first filtered through a 0.45 μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by a spin coating method. The spin coating conditions were set as follows: low speed 500 r / min for 5 s, high speed 4000 r / min for 30 s, and then the film was placed in front of a 70°C heating table and baked for 5 min to remove most of the solvent, thereby obtaining a 1 μm thick polymer film with a non-sticky surface; then, the top of the polymer film was shielded with a mask and placed under a central emission wavelength of 334 nm and an ultraviolet light intensity of 50 mW / cm 2 The film was exposed to an ultraviolet mercury lamp for 180 seconds, then developed at room temperature with a mixed solution of ethanol and water in a volume ratio of 6:5 as a developer for 25 seconds, then washed with deionized water, and finally dried at 80°C for 5 minutes to obtain a polyamic acid film with a clear cured pattern and good adhesion to the substrate; the polyamic acid film was imidized according to the following procedure: heated from 20°C to 300°C at a rate of 20°C / min in a nitrogen atmosphere, and maintained at 100°C, 200°C, and 300°C for 1 hour respectively, and finally cooled naturally to room temperature to obtain a polyimide film with a patterned surface.
[0078] Example 10
[0079] In a flask reaction vessel equipped with mechanical stirring and nitrogen atmosphere, 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.2809 g, 4.00 mmol) was dissolved in 9 mL N, N-dimethylacetamide, and continue to stir, after 2,2'-bis(trifluoromethyl)diaminobiphenyl is completely dissolved, hexafluorodianhydride (1.6319 g, 3.60 mmol) is added to the reaction solution in batches, and stirring is continued for 6 hours under ice-water bath conditions until the system presents a stable, transparent viscous solution; after the reaction is completed, nadic anhydride (0.1340 g, 0.80 mmol) is added to the reaction system, and stirring is continued for 4 hours; N, N-dimethylacetamide is added to the reaction solution to adjust the solid content of the solution to 28wt.%, and then trimethylolpropane tris(3-mercaptopropionate) (0.1181 g, 0.27 mmol) and photoinitiator benzoin dimethyl ether (102.5 mg, 0.40 mmol) are added to the reaction solution, and mechanical stirring is continued for 2 hours under light-proof conditions until all substances are evenly dispersed to obtain a photosensitive polyamic acid solution with photosensitivity;
[0080] The photosensitive polyamic acid solution was first filtered through a 0.45μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by spin coating. The spin coating conditions were set as follows: low speed 500r / min spin coating for 5s, high speed 4000r / min spin coating for 30s, and then the film was placed in front of a 70℃ heating table and baked for 5min to remove most of the solvent, obtaining a 1μm thick polymer film with a non-sticky surface. Then the polymer film was shielded with a mask and placed at a central emission wavelength of 334nm and an ultraviolet light intensity of 50mW / cm 2 The film was exposed to an ultraviolet mercury lamp for 180 seconds, then developed at room temperature with a mixed solution of ethanol and water in a volume ratio of 6:5 as a developer for 25 seconds, then washed with deionized water, and finally dried at 80°C for 5 minutes to obtain a polyamic acid film with a clear cured pattern and good adhesion to the substrate; the polyamic acid film was imidized according to the following procedure: heated from 20°C to 300°C at a rate of 20°C / min in a nitrogen atmosphere, and maintained at 100°C, 200°C, and 300°C for 1 hour respectively, and finally cooled naturally to room temperature to obtain a polyimide film with a patterned surface.
[0081] Embodiment 11
[0082] In a flask reaction vessel equipped with mechanical stirring and nitrogen atmosphere, 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.2809 g, 4.00 mmol) was dissolved in 8 mL of N,N-dimethylacetamide and stirred continuously. After 2,2'-bis(trifluoromethyl)diaminobiphenyl was completely dissolved, hexafluorodianhydride (1.5412 g, 3.40 mmol) was added to the reaction solution in batches and stirred continuously in an ice-water bath for 6 h until the system showed a stable, transparent, viscous solution. After the reaction is completed, naphthalene anhydride (0.2010 g, 1.20 mmol) is added to the reaction system, and the reaction is stirred continuously for 4 hours; N, N-dimethylacetamide is added to the reaction solution to adjust the solid content of the solution to 30 wt.%, and then trimethylolpropane tris (3-mercaptopropionate) (0.1771 g, 0.40 mmol) and photoinitiator benzoin dimethyl ether (153.8 g, 0.60 mmol) are added to the reaction solution, and mechanical stirring is continued for 2 hours under light-proof conditions until all substances are evenly dispersed to obtain a photosensitive polyamic acid solution with photosensitivity properties.
[0083] The photosensitive polyamic acid solution was first filtered through a 0.45 μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by a spin coating method. The spin coating conditions were set as follows: low speed 500 r / min for 5 s, high speed 4000 r / min for 30 s, and then the film was placed in front of a 70°C heating table and baked for 5 min to remove most of the solvent, thereby obtaining a 1 μm thick polymer film with a non-sticky surface; then, the top of the polymer film was shielded with a mask and placed under a central emission wavelength of 334 nm and an ultraviolet light intensity of 50 mW / cm 2 The film was exposed to an ultraviolet mercury lamp for 180 seconds, then developed at room temperature with a mixed solution of ethanol and water in a volume ratio of 6:5 as a developer for 25 seconds, then washed with deionized water, and finally dried at 80°C for 5 minutes to obtain a polyamic acid film with a clear cured pattern and good adhesion to the substrate; the polyamic acid film was imidized according to the following procedure: heated from 20°C to 300°C at a rate of 20°C / min in a nitrogen atmosphere, and maintained at 100°C, 200°C, and 300°C for 1 hour respectively, and finally cooled naturally to room temperature to obtain a polyimide film with a patterned surface.
[0084] Comparative Example 1
[0085] In a flask reaction container equipped with mechanical stirring and nitrogen atmosphere, 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.2809 g, 4.00 mmol) was dissolved in 10 mL of N,N-dimethylacetamide and stirred continuously. After 2,2'-bis(trifluoromethyl)diaminobiphenyl was completely dissolved, hexafluorodianhydride (1.7225 g, 3.80 mmol) was added to the reaction solution in batches, and stirred continuously for 6 h in an ice-water bath until the system presented a stable, transparent, viscous solution. N,N-dimethylacetamide was added to adjust the solid content of the solution to 26 wt %. Trimethylolpropane tris(3-mercaptopropionate) (0.0595 g, 0.13 mmol) and photoinitiator benzoin dimethyl ether (51.3 mg, 0.20 mmol) were added to the reaction solution, and mechanical stirring was continued for 2 h under light-proof conditions until all substances were evenly dispersed to obtain a polymer solution.
[0086] The polymer solution was first filtered through a 0.45 μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by a spin coating method. The spin coating conditions were set as follows: low speed 500 r / min for 5 s, high speed 4000 r / min for 30 s, and then the film was placed in front of a 70°C heating table and baked for 5 min to remove most of the solvent, thereby obtaining a 1 μm thick polymer film with a non-sticky surface; then, the top of the polymer film was shielded with a mask and placed under a central emission wavelength of 334 nm and an ultraviolet light intensity of 50 mW / cm 2 The sample was exposed to an ultraviolet mercury lamp for 180 seconds, then developed for 25 seconds at room temperature using a mixed solution of ethanol and water in a volume ratio of 6:5 as a developer, then washed with deionized water, and finally dried at 80°C for 5 minutes. The comparative example 1 was found through the above experimental process that the polymer did not remain on the quartz substrate after washing, indicating that no cross-linking behavior was generated, that is, no film was formed on the quartz substrate.
[0087] Comparative Example 2
[0088] In a flask reaction vessel equipped with mechanical stirring and nitrogen atmosphere, 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.2809 g, 4.00 mmol) was dissolved in 10 mL N, N-dimethylacetamide, and continue to stir, after 2,2'-bis(trifluoromethyl)diaminobiphenyl is completely dissolved, hexafluorodianhydride (1.7225 g, 3.80 mmol) is added to the reaction solution in batches, and stirring is continued for 6 hours under ice-water bath conditions until the system presents a stable, transparent viscous solution; after the reaction is completed, nadic anhydride (0.0335 g, 0.20 mmol) is added to the reaction system, and stirring is continued for 4 hours; N, N-dimethylacetamide is added to the reaction solution to adjust the solid content of the solution to 26 wt.%, and then trimethylolpropane tris(3-mercaptopropionate) (0.0595 g, 0.13 mmol) and photoinitiator benzoin dimethyl ether (51.3 mg, 0.20 mmol) are added to the reaction solution, and mechanical stirring is continued for 2 hours under light-proof conditions until all substances are evenly dispersed to obtain a photosensitive polyamic acid solution with photosensitivity;
[0089] The photosensitive polyamic acid solution was first filtered through a 0.45 μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by a spin coating method. The spin coating conditions were set as follows: low speed 500 r / min for 5 s, high speed 4000 r / min for 30 s, and then the film was placed in front of a 70°C heating table and baked for 5 min to remove most of the solvent, thereby obtaining a 1 μm thick polymer film with a non-sticky surface; then, the top of the polymer film was shielded with a mask and placed under a central emission wavelength of 334 nm and an ultraviolet light intensity of 50 mW / cm 2 The film was exposed to an ultraviolet mercury lamp for 180 seconds, then developed at room temperature with a mixed solution of ethanol and water in a volume ratio of 6:5 as a developer for 25 seconds, then washed with deionized water, and finally dried at 80°C for 5 minutes to obtain a polyamic acid film with a clear cured pattern and good adhesion to the substrate; the polyamic acid film was imidized according to the following procedure: heated from 20°C to 300°C at a rate of 20°C / min in a nitrogen atmosphere, and maintained at 100°C, 200°C, and 300°C for 1 hour respectively, and finally cooled naturally to room temperature to obtain a polyimide film with a patterned surface.
[0090] Comparative Example 3
[0091] In a flask reaction vessel equipped with mechanical stirring and nitrogen atmosphere, 2,2'-bis(trifluoromethyl)diaminobiphenyl (1.2809 g, 4.00 mmol) was dissolved in 10 mL N, N-dimethylacetamide, and continued to stir, after 2,2'-bis(trifluoromethyl)diaminobiphenyl was completely dissolved, hexafluorodianhydride (1.7225 g, 3.80 mmol) was added to the reaction solution in batches, and continued to stir for 6 h under ice-water bath conditions until the system presented a stable, transparent viscous solution; after the reaction was completed, nadic anhydride (0.2010 g, 1.20 mmol) was added to the reaction system, and continued to stir the reaction for 4 h; N, N-dimethylacetamide was added to the reaction solution to adjust the solid content of the solution to 26 wt.%, and then trimethylolpropane tris(3-mercaptopropionate) (0.0595 g, 0.13 mmol) and photoinitiator benzoin dimethyl ether (51.3 mg, 0.20 mmol) were added to the reaction solution, and mechanical stirring was continued for 2 h under light-proof conditions until all substances were evenly dispersed to obtain a photosensitive polyamic acid solution with photosensitivity;
[0092] The photosensitive polyamic acid solution was first filtered through a 0.45 μm polytetrafluoroethylene membrane to remove impurities, and then the polyamic acid solution was coated on a quartz substrate by a spin coating method. The spin coating conditions were set as follows: low speed 500 r / min for 5 s, high speed 4000 r / min for 30 s, and then the film was placed in front of a 70°C heating table and baked for 5 min to remove most of the solvent, thereby obtaining a 1 μm thick polymer film with a non-sticky surface; then, the top of the polymer film was shielded with a mask and placed under a central emission wavelength of 334 nm and an ultraviolet light intensity of 50 mW / cm 2 The film was exposed to an ultraviolet mercury lamp for 180 seconds, then developed at room temperature with a mixed solution of ethanol and water in a volume ratio of 6:5 as a developer for 25 seconds, then washed with deionized water, and finally dried at 80°C for 5 minutes to obtain a polyamic acid film with a clear cured pattern and good adhesion to the substrate; the polyamic acid film was imidized according to the following procedure: heated from 20°C to 300°C at a rate of 20°C / min in a nitrogen atmosphere, and maintained at 100°C, 200°C, and 300°C for 1 hour respectively, and finally cooled naturally to room temperature to obtain a polyimide film with a patterned surface.
[0093] Performance Test:
[0094] (I) Thermogravimetric analysis and differential scanning calorimetry analysis of polyimide films:
[0095] The thermal decomposition temperature of the polyimide films prepared in Examples 1 to 7 and Comparative Examples 1 to 3 was tested using a thermogravimetric analyzer. The experimental measurement conditions were: heating from 40°C to 800°C at a rate of 10°C / min in a nitrogen atmosphere, the mass of the sample was 5 mg, and the temperature at which the thermal weight loss of 5% occurred and the residual mass percentage at 750°C were recorded as T d5% and R w750 .
[0096] The glass transition temperatures (T g ) was tested. The experimental conditions were as follows: sample mass 5 mg to 10 mg, nitrogen atmosphere, nitrogen flow rate 50 mL / min, heating from room temperature to 400 °C at a rate of 20 °C / min, maintained for 5 min, then cooled to 40 °C, and again heated to 400 °C at a rate of 20 °C / min, nitrogen flow rate 50 mL / min. The second heating curve was used to measure the T g .
[0097] The specific test results are shown in Table 1 below.
[0098] Table 1:
[0099] Test Case <![CDATA[T g (℃)]]> <![CDATA[T d5% (℃)]]> <![CDATA[R w750 (%)]]> Example 1 292 555.8 59.52 Example 2 304 509.1 53.02 Example 3 322 434.0 49.82 Example 4 306 387.3 46.95 Example 5 305 502.2 52.83 Example 6 353 568.4 56.15 Example 7 290 439.7 0 Comparative Example 1 304 508.3 52.87 Comparative Example 2 303 508.1 53.06 Comparative Example 3 305 506.2 52.09
[0100] It can be seen from Table 1 that the negative photosensitive polyimide films of Examples 1 to 7 show excellent thermal properties in the above tests; wherein, the glass transition temperatures of the seven negative photosensitive polyimide films are ≥290°C, the temperature of 5% thermal weight loss is ≥387.3°C, and can be as high as 555.8°C. At the same time, the polymers obtained in Examples 1 to 6 have a residual mass percentage of ≥46.95% at 750°C, and the polyimide in Example 7 is a fully alicyclic structure, which is completely decomposed when calcined at a high temperature of 680°C; and Comparative Examples 1 to 3 are based on Example 2, but the content of the end-capping agent is changed. After thermal analysis, it can be found that the thermal properties are similar to those of Example 2, which shows that the polyimide film of the present application can still maintain the excellent thermal properties of the polyimide after the chemical structure is improved, and the addition of the end-capping agent hardly affects the material properties.
[0101] It can be seen that the negative photosensitive polyimide film prepared by the method of the present application can retain the thermal performance advantages of polyimide to the greatest extent, which is related to the high thermal stability of the chemical structure of the naphthalene dianhydride used for end-capping; this can also further improve the performance of the film after photocuring and patterning operations, and is expected to be used in a variety of high-temperature extreme scene conditions; in addition, it should be noted that in the preparation method of the present application, the amount of naphthalene dianhydride used for end-capping is small, which means that there are fewer components that decompose during the subsequent curing process, that is, the negative photosensitive polyimide film has a higher film retention rate.
[0102] like Figure 1 Shown are the thermal gravimetric curves of the negative photosensitive polyimide films prepared in Example 1 to Example 4; it can be clearly observed from the intersection of the four thermal gravimetric curves and the blue dotted line in the figure that the temperature at which the four negative photosensitive polyimide films experience a thermal gravimetric loss of 5% is around 400°C, that is, the decomposition temperature of the negative photosensitive polyimide film is high, that is, the thermal stability is good.
[0103] like Figure 2 Shown are the differential scanning calorimetry analysis curves of the negative photosensitive polyimide films prepared in Example 1 to Example 4; it can be seen from the figure that the glass transition temperatures of the four negative photosensitive polyimide films are around 300°C, that is, the negative photosensitive polyimide films have a high heat resistance temperature, that is, good thermal stability.
[0104] (II) Photosensitivity test:
[0105] Polarized light micrographs of the polyimide films with patterned surfaces prepared in Examples 8 to 11 and Comparative Examples 1 to 3 were collected using a polarized light microscope for characterization.
[0106] like Figure 3 The negative photosensitive polyimide photolithography line patterns of Examples 8 to 11 are shown. Figure 4 The negative photosensitive polyimide photolithography line patterns of Comparative Examples 1 to 3 are shown; wherein, Figure 3 The photo in part a shows the negative photosensitive polyimide photolithography line pattern of Example 8, the photo in part b shows the negative photosensitive polyimide photolithography line pattern of Example 9, the photo in part c shows the negative photosensitive polyimide photolithography line pattern of Example 10, and the photo in part d shows the negative photosensitive polyimide photolithography line pattern of Example 11; Figure 4 The photograph in part a shows the negative photosensitive polyimide lithography line pattern of comparative example 1, the photograph in part b shows the negative photosensitive polyimide lithography line pattern of comparative example 2, and the photograph in part c shows the negative photosensitive polyimide lithography line pattern of comparative example 3.
[0107] Depend on Figure 3 It can be seen that the negative photosensitive polyimide prepared by the preparation method of the present application can prepare different photolithography line patterns on a film with a thickness of 1 μm; specifically, Figure 3 The resolution of the photolithography lines in the photos shown in parts a-c is 10 μm. Figure 3 The resolution of the photolithography line in the photo shown in part d is 20 μm. In addition, it should be noted that in the preparation process of the above embodiments, the intensity of the ultraviolet light used for radiation cross-linking is 50 mW / cm 2 , is at a lower level, therefore, combined Figure 3 The photolithography line resolution shown also indicates that the negative photosensitive polyimide material prepared by the method of the present application has a high sensitivity to ultraviolet light.
[0108] Compared with Example 2, in the process of preparing the polyimide film in Comparative Example 1, no end-capping with naphthalene anhydride was used, resulting in the absence of cross-linking sites on the polymer. Furthermore, after the final cleaning step, no residue was left on the quartz substrate, indicating that no cross-linking behavior occurred and no film was formed on the quartz substrate.
[0109] Compared with Example 2, in the process of preparing the polyimide film in Comparative Example 2, the amount of norbornene diacid anhydride used for end-capping is outside the range specified by the method of the present application, specifically, the amount added is insufficient; this difference results in that although the polymer obtained by the polyimide prepared in Comparative Example 2 can exhibit patterned behavior, due to the insufficient amount of end-capping agent added, the resolution of the obtained patterned film is extremely low.
[0110] Compared with Example 2, in the process of preparing the polyimide film in Comparative Example 3, the amount of nadic anhydride used for end-capping is outside the range specified by the method of the present application, specifically, the amount added is excessive; this difference results in the polyimide prepared in Comparative Example 2 being unable to obtain a striped pattern with clear boundaries.
[0111] In summary, in the preparation method of the present application, the addition of nadic anhydride for end-capping and the control of the added amount have an important influence on the photosensitivity of the polyimide finally prepared; when the amount of nadic anhydride for end-capping is insufficient, sufficient cross-linking points cannot be added to the polyamic acid molecular chain, cross-linking curing cannot be effectively achieved, and the degree of cross-linking is low, resulting in a decrease in the resolution of the formed photolithography pattern; and when the amount of nadic anhydride for end-capping is excessive, free small molecule nadic anhydride exists in the system, which cross-links with the polythiol to form a small molecule system, resulting in the inability to achieve effective patterning.
[0112] In summary, the photosensitive resin disclosed in the present invention can not only be widely used in the field of preparing materials such as photoresists, photosensitive encapsulation adhesives, and photocurable adhesives, but also be applied in the field of preparing photoresists to form a solution-developable negative photosensitive polyimide system. Cross-linking points are constructed by utilizing the click reaction between the olefinic group of the polyamic acid end chain and the thiol group of polythiol, thereby reducing the solubility of the polyamic acid in the exposed area in the alkaline solution, thereby obtaining a negative pattern with high pattern resolution and sensitivity, and is expected to be well applied in the fields of optics and electronics.
[0113] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A negative photosensitive polyamic acid, characterized in that: Its chemical structure is as follows: In the formula, X is derived from a diamine monomer having at least one benzene ring or a cycloalkane structure; Y is derived from a tetracarboxylic dianhydride compound having at least one benzene ring or a cycloalkane structure; and the value of n ranges from 50 to 300.
2. The negative photosensitive polyamic acid according to claim 1, characterized in that: In the diamine monomer, X adopts at least one of the following chemical structures: In the tetracarboxylic dianhydride compound, Y adopts at least one of the following chemical structures:
3. A method for preparing a negative photosensitive polyamic acid as claimed in claim 1, characterized in that: The steps are: placing a mixed reaction liquid of a diamine monomer and a tetracarboxylic dianhydride compound in a nitrogen atmosphere and an ice-water bath environment to react for 6 hours to 12 hours; continuing to add norbornene dicarboxylic anhydride and reacting for 3 hours to 6 hours to cap; wherein the molar ratio of the diamine monomer to the tetracarboxylic dianhydride compound is 1:(0.85-0.99), and the sum of the molar amount of the anhydride of the tetracarboxylic dianhydride compound and the molar amount of the norbornene dicarboxylic anhydride is equal to the molar amount of the amino group of the diamine monomer.
4. The method for preparing a negative photosensitive polyamic acid according to claim 3, characterized in that: The solvent for preparing the mixed reaction liquid of the diamine monomer and the tetracarboxylic dianhydride compound is an organic solvent selected from one or more of N,N-dimethylacetamide, N,N-dimethylformamide or N-methylpyrrolidone; the amount of the organic solvent is such that the solid content of the mixed reaction liquid is 20wt% to 40wt%.
5. A photosensitive resin, characterized in that: include: Negative photosensitive polyamic acid, which is the negative photosensitive polyamic acid as claimed in claim 1 or 2, or the negative photosensitive polyamic acid obtained by the preparation method as claimed in claim 3 or 4; A polythiol, which is at least one of trimethylolpropane tris(3-mercaptopropionate) or pentaerythritol tetrakis(3-mercaptopropionate); the molar ratio of norbornene dicarboxylic anhydride to the polythiol used to prepare the negative photosensitive polyamic acid is (1-4):1; The photoinitiator is at least one of benzoin dimethyl ether, Michler's ketone, 2,2-dimethoxy-2-phenylacetophenone, acyl phosphine, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone, azobisisobutyronitrile, benzophenone, bisazide compounds, and 1-[4-(thio)phenyl]-2-(O-benzoyloxime)-1,2-octanedione; the amount of the photoinitiator added is 50% of the molar amount of norbornene dicarboxylic anhydride.
6. A method for preparing a photosensitive resin as claimed in claim 5, characterized in that: The steps are: (1) preparing a negative photosensitive polyamic acid into a mixed solution having a solid content of 24 wt % to 30 wt %; (2) Add polythiol and photoinitiator, and stir at room temperature in the dark for 1 h to 2 h.
7. An application of the photosensitive resin as claimed in claim 5, characterized in that: Used in the preparation of photoresists, photosensitive packaging adhesives, and photocuring adhesives.
8. A photosensitive polyimide film, characterized in that: It is formed of the photosensitive resin as claimed in claim 5.
9. A method for preparing a patterned polyimide film using the photosensitive resin as claimed in claim 5, characterized in that: The steps are: (1) coating a photosensitive resin on a substrate by spin coating; (2) using a mask to partially shield the spin-coated substrate and perform UV light cross-linking and curing; (3) washing and developing the cross-linked cured film using a developer; (4) The developed cross-linked cured film is subjected to imidization reaction to prepare a patterned polyimide film.
10. The method for preparing a patterned polyimide film formed from a photosensitive resin according to claim 9, characterized in that: In step (1), the steps of the spin coating film forming method are: drop the polyamic acid solution to the center of the substrate and let it stand for 5s to 20s. After the polyamic acid solution stops flowing, a coating machine with a substrate is placed on it and spin-coated at a low speed of 300r / min to 1000r / min for 5s to 15s, and then spin-coated at a high speed of 1100r / min to 5000r / min for 30s to 45s to form a negative photosensitive polyamic acid film; in step (2), the steps of implementing the imidization reaction are: heating from 20°C to 300°C at a rate of 20°C / min under a nitrogen atmosphere, and maintaining the temperatures at 100°C, 200°C, and 300°C for 1h respectively, and then naturally cooling to room temperature to obtain a polyimide film.
Citation Information
Cited By
High-compactness special film and preparation method thereof
CN121362442A
Low-temperature curing photoresist composition and preparation method thereof
CN122172507A